-12(k-1)=-(3k-6)

Simple and best practice solution for -12(k-1)=-(3k-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12(k-1)=-(3k-6) equation:


Simplifying
-12(k + -1) = -1(3k + -6)

Reorder the terms:
-12(-1 + k) = -1(3k + -6)
(-1 * -12 + k * -12) = -1(3k + -6)
(12 + -12k) = -1(3k + -6)

Reorder the terms:
12 + -12k = -1(-6 + 3k)
12 + -12k = (-6 * -1 + 3k * -1)
12 + -12k = (6 + -3k)

Solving
12 + -12k = 6 + -3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '3k' to each side of the equation.
12 + -12k + 3k = 6 + -3k + 3k

Combine like terms: -12k + 3k = -9k
12 + -9k = 6 + -3k + 3k

Combine like terms: -3k + 3k = 0
12 + -9k = 6 + 0
12 + -9k = 6

Add '-12' to each side of the equation.
12 + -12 + -9k = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -9k = 6 + -12
-9k = 6 + -12

Combine like terms: 6 + -12 = -6
-9k = -6

Divide each side by '-9'.
k = 0.6666666667

Simplifying
k = 0.6666666667

See similar equations:

| 9w+10w-8w= | | 2x+8-7x=48 | | 7z-5z-4z= | | 20+20+3g+2g=115 | | x(2)=-121 | | 2x+3=19-3x | | 2b+4b+5b= | | 8+3x+2x=23 | | 5(x-4)+2(x+1)=3(2-4) | | 14-2q-5=-2q+9 | | -8v-4v= | | -3*-5=51 | | 8g-2g= | | p=45-q | | 9q+(-4q)= | | 92=4+6w+2w | | 7w+4w= | | 8p+(-6p)+6m= | | 6r+5t+4r= | | 8e+3(5+e)=10 | | 6x+8(2x+3)= | | 2x+3+3x+2=180 | | 5(x-6)+8=7x-10 | | 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= |

Equations solver categories